2019
DOI: 10.3389/fnbeh.2019.00187
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Sexual Motivation in Rodents: Some Caveats

Abstract: Sexual behavior is activated by motivation. An overwhelming majority of experimental studies of the intricacies of sexual motivation has been performed in rodents, most of them in rats. Sometimes it is desirable to generalize results obtained in this species to other species, particularly the human. It is hoped that studies of the neurobiology of rodent sexual behavior may shed light on the central nervous mechanisms operating in the human, and the search for efficient pharmacological treatments of human sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 172 publications
(204 reference statements)
0
17
0
Order By: Relevance
“…Male sexual behavior can be categorized into either appetitive or consummatory behaviors (reviewed in Hull and Dominguez, 2015;Bialy et al, 2019;Le Moëne and Ågmo, 2019). In rodents, this begins with appetitive sexual behavior where the male examines the face and anogenital region of the female (Angoa-Pérez and Kuhn, 2015), followed by the consummatory sexual behaviors of mounting the female's rear and then intromitting several times until they ejaculate (reviewed in Angoa-Pérez and Kuhn, 2015; Hull and Dominguez, 2015;Bialy et al, 2019).…”
Section: Rodent Male Sexual Behaviormentioning
confidence: 99%
“…Male sexual behavior can be categorized into either appetitive or consummatory behaviors (reviewed in Hull and Dominguez, 2015;Bialy et al, 2019;Le Moëne and Ågmo, 2019). In rodents, this begins with appetitive sexual behavior where the male examines the face and anogenital region of the female (Angoa-Pérez and Kuhn, 2015), followed by the consummatory sexual behaviors of mounting the female's rear and then intromitting several times until they ejaculate (reviewed in Angoa-Pérez and Kuhn, 2015; Hull and Dominguez, 2015;Bialy et al, 2019).…”
Section: Rodent Male Sexual Behaviormentioning
confidence: 99%
“…Due to practical constraints, a large part of our knowledge about the biology of sexual orientation is derived from observing animals. It is important to generalize from animals to humans very cautiously (73,74). Theoretical models and hypotheses, like the model presented here, are crucial stages of the Scientific Method, and are usually employed for optimizing such generalizations and for the exploration of new ideas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above parameters, the total number of mounts (TMF), of intromissions (TIF) and of ejaculations (EF) in the whole 60 min period of copulation, the total copulatory rate (TCR), calculated by dividing the sum of all the activity periods of the male with the female rat (an activity period was defined from the first mount/intromission in a series of copulatory activity until ejaculation in that series) by the sum of all mounts and intromissions of the whole test and the total intromission ratio (TIR) calculated as the TIF divided by the sum of TIF and TMF were also calculated. Moreover, the number of noncontact penile erections (NCPEs), counted during the 30 min period in which the receptive female rat was inaccessible to the male during the microdialysis experiment (see below), was also recorded (Sachs and Barfield, 1976;Melis et al, 2003;Sanna et al, 2014aSanna et al, ,b, 2015aSanna et al, ,b, 2017bSanna et al, , 2019Le Moëne and Ågmo, 2019). Finally, since substantial differences in genital self-grooming, a centrally-mediated, self-directed highly stereotyped behavior that in the context of copulation may indicate self-cleaning and/or self-stimulation (Sachs et al, 1988;Berridge et al, 2005), were observed among the three rat lines during the five copulatory tests, the percent of mounts, intromissions, and ejaculations followed by genital grooming as well as the frequency and duration of genital grooming episodes after mounts, intromissions and ejaculation were recorded for each animal in the first series of copulatory activity during the microdialysis experiment (Sachs et al, 1988).…”
Section: Sexual Behaviormentioning
confidence: 99%